2018
DOI: 10.21873/anticanres.12685
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of p53 and Rb Pathways Are Associated with High Proliferation in Bladder Urothelial Carcinomas

Abstract: The results showed that a) alterations of the p53 and Rb pathways are associated with high proliferation of tumor cells in BUC and b) high expression of cell-cycle proteins is associated with adverse histopathological parameters of these tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…A more recent study of 413 high grade muscle invasive bladder malignancies found that the RB gene, RNA or protein expression was altered in 17% of the malignancies [ 20 ]. Bladder malignancies with alterations in the RB and p53 pathways have been noted to have high proliferation rates [ 21 ]. In addition to a mutation, deletion or epigenetic silencing of the RB gene, the RB tumor suppressive pathway can be circumvented by overexpression of cyclin D, Cyclin D which along with its binding partners CDK4/6 hyperphosphorylates RB, thus disabling its tumor suppressive activity.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study of 413 high grade muscle invasive bladder malignancies found that the RB gene, RNA or protein expression was altered in 17% of the malignancies [ 20 ]. Bladder malignancies with alterations in the RB and p53 pathways have been noted to have high proliferation rates [ 21 ]. In addition to a mutation, deletion or epigenetic silencing of the RB gene, the RB tumor suppressive pathway can be circumvented by overexpression of cyclin D, Cyclin D which along with its binding partners CDK4/6 hyperphosphorylates RB, thus disabling its tumor suppressive activity.…”
Section: Introductionmentioning
confidence: 99%
“…RUNX3, SRFP1, and E‐cadherin are related to WNT/beta‐catenin pathway, and the methylation is related to proliferation and lymph node metastasis, poor prognosis, and tumor stage 28–30 . p16INK4a inhibits cyclin‐dependent kinases (CDK) CDK4 and CDK6, and thereby preventing G1‐to‐S cell‐cycle phase progression; thus, the methylation of p16INK4a is reported cell‐cycle progression 31 . As well as, the inhibition of DNMT1 leads to the activation of p16, RUNX3, SFRP1, and E‐cadherin 29,32–34 .…”
Section: Discussionmentioning
confidence: 99%
“…25 A more recent study reported that the X chromosome protects against BCa via upregulation of the canonical P53 pathway. 26 We and others found that p53 mutation has a significant impact on BCa outcome, [27][28][29] suggesting that both STAG2 and P53 mutations are associated with BCa recurrence and progression. Previous studies on the relationship between STAG2…”
Section: Introductionmentioning
confidence: 93%